ANALISIS PENERAPAN METODE TUNJANGAN PAJAK (GROSS UP) PAJAK PENGHASILAN PASAL 21 TERHADAP LABA RUGI FISKAL DI BADAN PENGELOLA KESEJAHTERAAN KRAKATAU STEEL TAHUN 2018 - RIKA KARTIKA; RATU SIFA NI’MAH; RISALDY ARDIPUTRA (JURNAL ILMIAH KOHESI, 2020)
The background in this study is a factor of PT. Krakatau Steel for its massive efficiency throughout Krakatau Steel Group environment, and the rise of BPJS Kesehatan dues. This research is to find out whether the income tax calculation of article 21 using the Gross up method is most efficient than on the net method used by Bapelkes and its impact on cash flows and fiscal income loss including the income tax agency at Bapelkes Krakatau Steel. The data used in this research is the secondary data obtained in the finished form or data that has been processed through documentation, observation data and interviews. The secondary Data used in this study is employee payroll, calculation of Income Tax Article 21 year 2018 and Fiscal income calculation year 2018. While the method of analysis used in this research is a method of descriptive analysis with a qualitative approach. The results of this research show that from the method of calculation of income tax article 21 using Gross up method is the most efficient or the provision of benefits for tax loss, but because the gross circulation income bapelkes does not exceed 50 billion per year so the amount owed on the body income tax is smaller than the income tax instalments article 25. So it is better to use the net method for the case in the Bapelkes Krakatau steel, except when the income criteria in a year and the number of employees in Bapelkes has increased. The next solution is to mix net and gross up calculations.